Rhabdomyolysis revisited: Detailed analysis of magnetic resonance imaging findings and their correlation with peripheral neuropathy. Issue 33 (August 2018) - Kim, Jun Ho; Kim, Yeo Ju; Koh, Sung Hye; Kim, Bom Soo; Choi, Sun Young; Cho, Seong Eun; Song, Joon Ho; Kim, Chang-Hwan; Lee, Kyung Hee; Cho, Soon Gu
Abstract : Abstract: The objective is to evaluate the magnetic resonance imaging (MRI) findings in rhabdomyolysis in detail and determine their correlation with the development of peripheral neuropathy. Magnetic resonance images for 23 patients with confirmed rhabdomyolysis with (n = 11) or without (n = 12) peripheral neuropathy were retrospectively reviewed for the signal intensity on T1- and T2-weighted images, intramuscular hemorrhage, enhancement pattern, shape and margin in the longitudinal plane, edema in the deep fascia and overlying subcutaneous layer, multiplicity, and bilateral limb involvement. The collected data were statistically analyzed and the relationship between the imaging findings and the development of peripheral neuropathy was determined. Abnormal signal intensities on T1- or T2-weighted images were observed for all patients except one. Fourteen patients (60.9%) showed intramuscular hemorrhage. Stippled enhancement (11/23; 47.8%) was the most common enhancement pattern. Nineteen patients (86.4%) showed a well-defined rectangular shape with a ragged margin in the longitudinal plane. The affected muscle volume usually increased (17/23; 73.9%), with edema in the deep fascia and the overlying subcutaneous layer (13/23; 56.5%). Multiplicity within a muscle, compartment, and limb was observed in 7 (31.8%), 18 (81.8%), and 16 (72.7%) patients, respectively. Bilateral involvement was observed in 7 patients (30.4%). Only multiplicity within a compartment showed a statistically significant correlation with peripheral neuropathy development. Common MRI findings in rhabdomyolysis include intramuscular hemorrhage, stippled enhancement, a well-defined rectangular shape with a ragged margin in the longitudinal plane, and multiplicity. Multiplicity within a compartment may be a predictor of the development of peripheral neuropathy.